Board gender dominated sectors and financial performance in sri lanka - Hameed, Z.; Senavirathna, N.; Weerasooriya, S.; Yasarathna, D.; Jayathilaka, R. (University of Jaffna, 2019)
The purpose of this study is to identify the relationship between percentage of women on board and firm financial performance. In order to investigate this relationship, the gender composition of corporate boards of the 20 sectors classified by the Colombo Stock Exchange (CSE) is compared against its financial performances using Return on Assets (ROA) as a proxy. Data collected was analyzed using Pearson correlation technique. The results revealed new insights: The percentage of women directors in Information and Investment sectors has both a positive and significant correlation with the ROA. Moreover, the Information sector has the strongest positive relationship between the women director’s percentage and ROA, while the Telecommunication sector has the strongest negative relationship.
Keywords: Women directors; financial performance; Colombo stock exchange